Characterization and Fitness Cost of Tn7100, a Novel Integrative and Conjugative Element Conferring Multidrug Resistance in Haemophilus influenzae - Johannessen, Helene; Anthonisen, Inger Lill; Zecic, Nermin; Hegstad, Kristin; Ranheim, Trond Egil; Skaare, Dagfinn (Frontiers in Microbiology, 2022)
A multidrug-resistant (MDR) strain of H. influenzae, Hi-228, with phenotypic resistance towards ampicillin, cefotaxime, chloramphenicol, gentamicin, and azithromycin, was isolated in Oslo, Norway. The strain was part of a clonal outbreak (2016-2017) comprising five ST143 strains with identical resistotypes. Hi-228 carries a novel integrative and conjugative element (ICE), Tn7100, contributing to this remarkable and previously unreported MDR profile. Tn7100 contains the following resistance genes; blaTEM-1B, catA2, aac(6’)-Im, aph(2’’)-Ib, mef(E), and mel. The latter four are previously unreported or rarely reported in H. influenzae. In this study we investigated the genetic environment, mechanisms of transfer, impact on phenotypic susceptibility, and fitness cost of this ICE. We found that Tn7100 has an overall structure similar to the previously described ICE Tn6686, with blaTEM-1B and catA2 carried by Tn3 and Tn10, respectively. The major difference between Tn7100 and Tn6686 is that Tn7100 lacks tet(B), but carries the resistance gene pairs aac(6’)-Im and aph(2’’)-Ib, and mef(E) and mel. The gene pairs are located on the novel transposable elements Tn7470 and Tn7471, which have high sequence identities to a plasmid in Enterobacterales and an ICE in streptococcal species, respectively. Tn7100 does circularize and is transferable, however at a low frequency. Head-to-head competition experiments showed that uptake of Tn7100 reduces bacterial fitness. Our study shows that MDR strains are capable of clonal spread, and that the H. influenzae supragenome comprises an increasingly wide range of transferable resistance genes, with evidence of transfer from unrelated genera. The findings offer a glimpse into the genome dynamics of H. influenzae, highlighting the importance of rational antibiotic usage to contain antimicrobial resistance and the emergence of MDR strains in this important pathogen.